Communicating Carbon - Harvey, Blane; Ensor, Jonathan; Carlile, Liz; Garside, Ben; Patterson, Zachary; Naess, Lars Otto (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Communicating Carbon is a workshop approach which brought together carbon project practitioners who are already working closely with farmers to discuss how to better communicate the concept, risks, and benefits of carbon initiatives aimed at smallholders – based around the principle of Free, Prior and Informed Consent (FPIC). These practitioners act as “brokers” between carbon buyers and farmers who may have the means to plant more trees or sequester more carbon in the soil to help offset emissions. Developing better communication tools and approaches is a way to ensure FPIC in carbon projects.